Impacts caused by polypharmacy on the elderly: an integrative review (Research, Society and Development, 2021)
Objective: To identify the impacts caused by polypharmacy in the elderly. Methodology: It was an descriptive review of a qualitative approach, with the researches carried out in the online database of the Regional Portal of the Virtual Health Library (VHL) and in its affiliated sites. Publications published between 2014 and 2018 were included, with full text, articles, monographs and theses in Portuguese and English, available free of charge, covering up to three descriptors used. Works with a date lower than 2014 were excluded, also those that presented only abstracts and citations with languages ​​other than those previously mentioned. The study consisted of an analysis of 9 publications. Results: it is evident that the use of various drugs combined or not with other forms of supplementary health care, is a common practice in the elderly and is often described in the literature as a current difficulty due to complications and their impact on health system costs. Conclusion: polypharmacy was perceived as a common problem in many elderly people. This is also due to the phenomenon of medicalization that is already rooted in our culture. Thus, with the passage of time, the elderly increasingly incorporate drugs into their daily lives, driven by the pharmaceutical industry, which due to its strong marketing, ensuring inputs of great relevance, makes these individuals use drugs concomitantly, many of the times from self-medication.